THE ROLE OF DIGITAL TECHNOLOGIES IN THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE TEACHERS - Ruzieva Dilafruz Raupovna (Bright Mind Publishing, 2025)
The article analyzes the importance of digital technologies as a necessary condition for the formation of the readiness of future teachers for methodological work, and also emphasizes the importance of paying special attention to the gradual introduction of information and communication technologies into the educational process and improving the system of training programmers in accordance with modern requirements.
Keywords: Continuous education, information, digital technologies, cloud technologies, artificial intelligence, digital educational resources, educational portals, website, competencies, knowledge, skills and qualifications.